NAVIGATING THE HURDLES OF TOEFL READING COMPREHENSION: INSIGHTS FROM UNIVERSITAS NEGERI GORONTALO - Muziatun Muziatun; Sartin T Miolo; Hildasari Abuda (Indonesian EFL Journal, 2024)
This study aims to identify and overcome the challenges faced by students at Universitas Negeri Gorontalo in the TOEFL reading comprehension section. Despite extensive research on TOEFL reading comprehension, there remains a gap in practical, context-specific interventions tailored to Indonesian EFL learners. This study utilizes a mixed-methods approach to address this gap. First, a needs analysis was conducted through surveys and interviews to identify key difficulties. Subsequently, various instructional strategies, including vocabulary enhancement and reading strategy training, were implemented and evaluated. The results indicate that targeted interventions significantly improve students' reading comprehension skills. The findings contribute to the broader field of language education by providing practical solutions for educators and students to navigate the hurdles of TOEFL reading comprehension.Keywords: TOEFL, reading comprehension, vocabulary mastery, instructional strategies, EFL learners, Indonesian context.